A review on heavy metal concentration in potable water sources in Nigeria: Human health effects and mitigating measures - Izah S.C.; Chakrabarty N.; Srivastav A.L. (My University, 2025)
Nigeria is one of the most populated black nation in the world with a population of about 170 million. Over the years, potable water source which is one of the basic essential requirements for healthy living has been challenging due to inadequate controlled anthropogenic activities and by lesser extent natural conditions. This paper reviews the various potable water sources, heavy metal concentration, and its associated health effects in Nigeria. The study found that surface water such as stream, river, lake; ground water including borehole and hand-dug well; rain water; and packaged water such as bottled and sachet are the major source of potable water. The dominant heavy metals found in potable water include iron, zinc, copper, chromium, lead, and manganese. The concentration of heavy metals like mercury, lead, cadmium, iron, cobalt, manganese, chromium, nickel, zinc, and copper often exceed the maximum permissible limit recommended by standard organization of Nigeria and World Health Organization. The concentration of heavy metals fluctuates in most states/geographical coverage depending on the type of potable water sources. To a large extent, industrialization causes heavy metals concentration to exceed the permissible limits. The high concentration reported in most locations could cause various disease conditions depending on the type of metal and level of exposure. This study also suggest possible treatment and mitigating measures to avoid such harmful effects. © Springer Science+Business Media Dordrecht 2016.